Augmented Reality Framework For Symbian Mobile Devices - Oui, Wei Wei (University Malaysia Sarawak, UNIMAS, 2013)
Nowadays, mobile devices are becoming an important part of our daily life. Augmented Reality (AR) is a technology that generates virtual information onto the real world to enhance user’s perception and interaction. AR technology can achieve it best performance when it can be mobilized. Therefore, mobile devices come in as a platform to deploy AR application. To make the development of AR application for mobile device more efficient, an Augmented Reality framework is developed in this research. The framework is targeted on Symbian mobile platform. It allows user build AR application by using the function provided. Mobile AR framework applied the concept of vision-based tracking and the development of mobile AR framework involved real time camera capturing, marker tracking (pose estimation) and virtual object rendering. Computer vision and computer graphics concepts are applied in the development of the framework. Open source libraries such as OpenGL and OpenCV are used to develop mobile AR framework. Optimized algorithms are used to ensure that AR application running smooth. Besides, this framework was able to use color marker for registration. Moreover, mobile AR framework can be port to other platform which support the open sources libraries used. The developed framework is tested for it efficiency and also performance under different conditions.